Integral-field observations of centaurus a nucleus - Krajnovic, D; Sharp, R; Thatte, N (2007)
We observed the nuclear region of Centaurus A in the J band with CIRPASS, mounted on GEMINI South telescope. Here we present the preliminary results focusing on the kinematic structure of the gas disk and present a simple model determining its kinematic orientation and inclination as well as an estimate of the mass of the central black hole.